Medical Students as Coaches in Transitions of Care for Youth With Special Health Care Needs - Nathan Bradford; Brian Mulroy (Association of American Medical Colleges, 2015)
Abstract Introduction On reaching adulthood, youth with special health care needs (YSHCN) face many difficult transitions including transition to adult medical care. In our setting, a population of YSHCN had historically been responsible for establishing their own adult care after graduating from a large pediatric practice. Barriers to effective transition include lack of transportation, intellectual limitations, lack of health insurance, caregiver stress, and inability to advocate for oneself. In addition, adult providers may face a lack of confidence and knowledge to assume care of these patients. In this project, we paired YSHCN with third-year medical students who served as coaches to assist the patients in transition. Methods Students meet their assigned YSHCN patient in the children's clinic for the patient's last appointment there, the exit visit. At that visit the student assists the patient and family in completion of two documents: (1) a validated Transition Readiness Checklist, a simple one-page checklist of tasks which the patient needs to master to achieve independence, and (2) a medical history summary, which indicates what other specialists and services the patient requires. The students then complete a pretest assessing their knowledge of problems and resources pertaining to transitioning YSHCN patients. Then the students attend a brief didactic presentation that outlines the complex needs of this population and the resources available. They were all given a handout with contact information for local services. After the study a posttest is given to assess knowledge gained, and the students submit a reflective essay. Results All YSHCN patients successfully attended their exit and entrance visit appointments. They or their caregivers completed readiness assessments at both appointments. Some modest goals were achieved. Student pre− and posttests were used to assess their learning of the core material. More importantly, the student essays showed significant gains in their understanding of the importance of fostering and encouraging self-advocacy and independence in this vulnerable population. Discussion This module gave third-year medical students the opportunity to act as coaches to facilitate the transition of a group of YSHCN who are moving care from a pediatric clinic to a family medicine practice. After implementation, students gained insight into the challenges facing these young people, as evidenced by their reflective narratives. Further, all the patients were successfully established in the Family Medicine Center. However, the additional time requirements for the project made it difficult for the students to be fully engaged.